Solid Waste Management Practice in Mymensingh Municipal Area, Bangladesh - Mian, MM; Paul, AK; Alam, MD; Rasheduzzaman, M; Saifullah, ASM (Journal of Environmental Science and Natural Resources, 2013)
The study was conducted to investigate the present solid waste management practice in Mymensingh municipal area especially in Ward 04 and 06. Huge solid wastes are generated every day in these wards but the waste management is not properly done because of their irregular waste management activities or unconsciousness. Maximum respondents discharged 1kg solid waste from their households per day and the respondents were 64%. Other 18% household discharged 0.5 kg and another 18% discharged 2 kg solid waste from their house per day. A majority percent of people dumps the produced solid waste in their living surroundings which produce various hazards in human health and environmental problems. This improper waste management can be managed by the regularity of management work, building awareness of the people and improving waste treatment. The municipality and other related NGOs should work together to solve these issues. It was revealed from the study that due to lack of people knowledge about solid waste management, lack of adequate budget for waste management, lack of available transport vehicles for waste management, lack of proper solid waste treatment plant etc. The total solid waste management system required following the recommendation which include proper planning, creating awareness, developing infrastructure, providing logistic support and finally involving NGOs, CBOs, public in this process. A sustainable solid waste management can be established which can lead the studied area to a healthy setting. DOI: http://dx.doi.org/10.3329/jesnr.v5i2.14813 J. Environ. Sci. & Natural Resources, 5(2): 193-198 2012